2012
DOI: 10.1103/physreve.85.026104
|View full text |Cite
|
Sign up to set email alerts
|

Conditional strategies and the evolution of cooperation in spatial public goods games

Abstract: The fact that individuals will most likely behave differently in different situations begets the introduction of conditional strategies. Inspired by this, we study the evolution of cooperation in the spatial public goods game, where besides unconditional cooperators and defectors, also different types of conditional cooperators compete for space. Conditional cooperators will contribute to the public good only if other players within the group are likely to cooperate as well, but will withhold their contributio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(82 citation statements)
references
References 55 publications
3
79
0
Order By: Relevance
“…In particular, evolutionary games in networks, spurred on by the seminal discovery of spatial reciprocity [12] and, subsequently, * szolnoki.attila@ttk.mta.hu by the discovery that scale-free networks strongly facilitate the evolution of cooperation [13,14], are still receiving ample attention to this day [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. One of the most recent contributions to the subject concerns the assignment of cognitive skills to individuals that engage in evolutionary games in networks [35,[38][39][40][41]. The earliest forerunners to these advances can be considered strategies such as "tit for tat" [42] and Pavlov [43], many of which were already proposed during the seminal experiments performed by Axelrod [44] and which assume that individuals have cognitive skills that exceed those granted to them in the framework of classical game theory.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, evolutionary games in networks, spurred on by the seminal discovery of spatial reciprocity [12] and, subsequently, * szolnoki.attila@ttk.mta.hu by the discovery that scale-free networks strongly facilitate the evolution of cooperation [13,14], are still receiving ample attention to this day [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. One of the most recent contributions to the subject concerns the assignment of cognitive skills to individuals that engage in evolutionary games in networks [35,[38][39][40][41]. The earliest forerunners to these advances can be considered strategies such as "tit for tat" [42] and Pavlov [43], many of which were already proposed during the seminal experiments performed by Axelrod [44] and which assume that individuals have cognitive skills that exceed those granted to them in the framework of classical game theory.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gächter, Kölle, and Quercia (2017) [11] found that framing the public good game as a Maintenance or a Provision problem affects the elicited contribution profiles. 5 Different kinds of framing effects have been shown to affect contributions in public good games (e.g., Andreoni 1995 [14]; Ellingsen et al, 2012 [15]; Dufwenberg et al 2011 [16]; Fosgaard, Hansen,Wengström, 2014 [17]; Nikiforakis, 2010 [18]). For an extensive list of references, see Cartwright (2016) [19].…”
Section: The Experimentsmentioning
confidence: 99%
“…In his essay on experimenter demand effects, Zizzo (2010, p. 85) [8] argued that the FGF method could overestimate the fraction of conditional cooperators in their sample by making subjects "think that conditionality was important". Although Zizzo (2010) [8] focused primarily on 1 For some recent theoretical contributions on the evolution of conditional cooperation, see Szolnoki and Perc (2012) [5], Szolnoki and Perc (2013) [6] and Zhang and Perc (2016) [7]. the possibility that the strategy method "may have clued in subjects that the experiment was about conditionality", a similar argument could be made about the ordering of others' contributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide literature in Experimental and Behavioral Economics try to understand the reason behind this behavior which seems to characterize human being. Using different kind of games such as Prisoner Dilemma, Ultimatum Game and Public Good Game, it has been shown that subjects do not behave as an homo oeconomicus but they are, on average, altruist in a bilateral game or they behave as an homo reciprocans in a multi-player setting (Szolnoki and Perc (2012), Tian et al (2016), Fehr and Gächter (1998)). …”
Section: Introductionmentioning
confidence: 99%